Pest Status of Gall Making Insect, Leptocybe invasa Fisher & Lasalle, in Nurseries and Plantations of Eucalyptus in Madhya Pradesh - Roychoudhury, N.; Chandra, Subhash; Singh, Ram Bhajan (Indian Forester, 2016)
The present paper reports the assessment of damage caused by gall insect Leptocybe invasa Fisher&LaSalle (Hymenoptera : Eulophidae) in eucalyptus. Based on the survey of forest nurseries and plantations of eucalyptus in Madhya Pradesh, the infestations of gall insect revealed wide variations in respect of age of seedlings and saplings. The infestation percentage of L. invasa varied from 20% in one month age of old seedlings and 100% in one year old seedlings in nurseries and 80-100% infestation was recorded in six months old plantations. The intensity of damage was observed to be very severe in seedlings and saplings. The production of galls in relation to early growth of seedlings revealed that there was an increase in number of galls formed irrespective of leaves, petioles and stems. The relative susceptibility to the gall insect varied among seed raised genotype and hybrid eucalyptus, which advocates the differential response of gall wasp in regard to genotype. All these observations clearly indicate that L. invasa is a major gall making insect pest of eucalyptus especially in seedling/sapling stage.